Design optimization of a rocket engine's inner liner with improved response surface methodology. Issue 7 (3rd July 2022) - Bouajila, Wissam; Shimoda, Masatoshi; Riccius, Joerg
Abstract : This article presents the optimization of the design of a subscale effusion-cooled rocket engine inner liner made of porous composite material, with the aim of improving the ability of the coolant film to protect the combustion chamber wall from thermochemical attacks. The optimization problem is defined as a global minimization problem and solved using response surface methodology (RSM). Recommendations to construct an efficient D -optimal design in a constrained design domain using design of experiments theory are provided. Computational fluid dynamics simulations are carried out to provide measurements of the response. The iteratively reweighted least squares method is used in the fit of the regression models to improve the efficiency of RSM with no additional cost. Enhanced coolant film properties for the optimal design show that the optimization problem was properly solved and the inner liner design was successfully optimized. These results demonstrate the efficiency of the optimization method.